Analysis of cases managed by the otolaryngology service in the Chinese military peacekeeping level 2 medical treatment facility in Mali. Issue 6 (11th June 2018) - Zhao, Yongqiang; Ma, X; Li, Y; Fu, Q
Abstract : Objectives: As part of the UN peacekeeping mission in Mali, the People's Republic of China have deployed a level 2 medical treatment facility (CHN L2). The aim of this study was to review the cases managed by the otolaryngology service within this facility. Methods: The medical records of all patients treated by the otolaryngology service at the CHN L2 from 1 March 2015 to 1 March 2018 were retrospectively assessed. Results: 614/10189 (6%) of all cases seen in the hospital during this period were referred to the otolaryngology service. 7/614 cases required admission to hospital (1.14%) and 40/614 cases required surgery (6.51%). 3/40 cases requiring surgery (7.5%) were performed under general anaesthesia and 37 cases (92.5%) were under local anaesthesia. The most common surgical treatment was facial soft-tissue injury debridement and closure. Acute rhinosinusitis was the most common diagnosis, followed by acute pharyngitis and allergic rhinitis. Four patients required medical evacuation to a level 3 medical treatment facility. Conclusions: Disease non-battle injury in the form of ear disease was the most common presentation. Maxillofacial soft-tissue injury was the most common cause of traumatic injury. There were limits that the service could provide in terms of medical equipment and consumables, necessitating increased training of otolaryngologists prior to deployment.